2019
DOI: 10.20489/intjecse.512387
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Mothers of Children with Special Needs in Early Childhood Inclusion

Abstract: Parents of young children with special needs in inclusion are among key stakeholders influencing the effectiveness of inclusion. There is significant evidence to suggest, however, that difficulties they encounter throughout inclusion hinder parents to perform their role as partners. This suggests that their role in their child's education would be highly limited unless their needs resulting from the challenges they face are not met. Meeting their needs would empower them in fulfilling their roles and increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…It was concluded that mainstreaming education could not be realized as desired due to reasons such as the physical structure of the school and the unsuitable class size, the unequal distribution of inclusion students to the classes, the demands of the classroom teachers not being met, insufficient material support, and insufficient inservice trainings despite the fact that the teachers received assistance from the training support teachers (Sarac and Colak 2012;Guzel 2014;Yaman 2017). When the studies were examined in general, it was found that classroom teachers emphasized that they did not find themselves sufficient about inclusion education, that support education services and material support were not provided, and that they wanted to improve themselves in relation to the education of students with special needs but they did not receive education support in this sense (Dagli and Oznacar, 2015;Germano, Brito and Capellini, 2017;Sardohan and Akcamete, 2018;Bayrakli and Sucuoglu, 2018). In order to be effective in mainstreaming education, it is of great importance to determine the actions of classroom teachers regarding instructional practice and evaluation, and to take necessary precautions and to provide the necessary support in this area.…”
Section: Determining Practices Of Classroom Teachers Who Have Mainstreaming and Special Needs Students In Their Classesmentioning
confidence: 99%
“…It was concluded that mainstreaming education could not be realized as desired due to reasons such as the physical structure of the school and the unsuitable class size, the unequal distribution of inclusion students to the classes, the demands of the classroom teachers not being met, insufficient material support, and insufficient inservice trainings despite the fact that the teachers received assistance from the training support teachers (Sarac and Colak 2012;Guzel 2014;Yaman 2017). When the studies were examined in general, it was found that classroom teachers emphasized that they did not find themselves sufficient about inclusion education, that support education services and material support were not provided, and that they wanted to improve themselves in relation to the education of students with special needs but they did not receive education support in this sense (Dagli and Oznacar, 2015;Germano, Brito and Capellini, 2017;Sardohan and Akcamete, 2018;Bayrakli and Sucuoglu, 2018). In order to be effective in mainstreaming education, it is of great importance to determine the actions of classroom teachers regarding instructional practice and evaluation, and to take necessary precautions and to provide the necessary support in this area.…”
Section: Determining Practices Of Classroom Teachers Who Have Mainstreaming and Special Needs Students In Their Classesmentioning
confidence: 99%
“…Early childhood intervention efforts with infants are best targeted at the level of the mother or primary caregiver of the infant. The infant’s mother is instrumental in the engagement of protective factors and mediation of risk factors, such as providing language stimulation to prevent or mediate a communication developmental delay (Bayrakli & Sukuoglu 2019 ; Ingber et al 2010 ). Additionally, it is well known that positive mother–infant interactions foster optimal developmental environments (Festante et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%